MODERN VERIFICATION CRITERIA AND BASIC PRINCIPLES OF THE MANAGEMENT OF NON-ALCOHOLIC FATTY LIVER DISEASE IN CHILDREN - O.A. Poda (Проблеми екології та медицини)
The article summarizes the knowledge about epidemiological data, clinical features, criteria for verification of the diagnosis, modern principles of diagnosis and treatment of non-alcoholic fatty liver disease (NAFLD) in children based on the analysis of literature sources using paper and electronic databases PubMed, CyberLeninka, Web of Science, MedLine, The Cochrane Library. A review of literary sources on the study of this pathology demonstrates that at the present stage NAFLD has become one of the most common causes of chronic liver disease in children and adolescents because of the growing worldwide epidemic of childhood obesity. The article presents the latest recommendations of the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition and the American Association for the Study of Liver Diseases on the screening strategy and basic criteria for verification of the diagnosis, as well as the principles of treatment of this pathology in pediatric practice. Particular attention is paid to the description of the main imaging methods that play a key role in the diagnosis of NAFLD in children and adolescents. The role of lifestyle modification as the main method of NAFLD treatment according to current international recommendations is described in detail. The review also analyzes the main researches that have focused on alternative treatments targeting the basic pathogenic factors of pathology development. In conclusion, the author considered the problem of lack of accurate non-invasive markers of hepatocellular damage and fibrosis in the pediatric practice, as well as the lack of clinical trials to determine optimal approaches to the treatment of non-alcoholic fatty liver disease in children.